Pre-eruptive intracoronal resorption in a 10-year-old girl: a review and case report - Laresh Naresh Mistry; Shreyas Neelkanthan; Anusree Basu (Frontiers in Oral Health)
Pre-Eruptive Intracoronal Resorption (PEIR) is a pathological condition characterized by the resorption of dental tissues within the crown of an unerupted tooth. It is typically asymptomatic and is most often identified incidentally during radiographic examinations. The exact etiology of PEIR remains unclear, although various theories have been proposed, including developmental disturbances, trauma, and genetic factors. This article aims to provide a comprehensive review of PEIR, following the Case Report (CARE) checklist, to enhance understanding and awareness of this dental anomaly.